Steady-state sustainment of divertor detachment with multi-species impurity seeding in LHD. (25th October 2021) - Mukai, Kiyofumi; Masuzaki, Suguru; Hayashi, Yuki; Oishi, Tetsutaro; Suzuki, Chihiro; Kobayashi, Masahiro; Tokuzawa, Tokihiko; Tanaka, Hirohiko; Tanaka, Kenji; Kinoshita, Toshiki; Sakai, Hikona; Peterson, Byron Jay
Abstract: Multi-species impurity seeding is an advanced operation scenario to mitigate the divertor heat load for the realization of future fusion reactors. In the large helical device, divertor detachment is successfully sustained using higher-Z (krypton, Kr) and lower-Z (neon, Ne) superimposed seeding. Emission from Kr impurities is drastically enhanced if it is followed by Ne seeding. Plasma radiation can be enhanced even at the upstream region in the edge plasma compared with Ne only seeded plasmas with suppression of impurity accumulation toward the central plasma. The characteristics of divertor heat load reduction and energy confinement are comparable between the Kr + Ne seeding and Ne only seeding under the same radiation fraction. However, while the detachment in Ne only seeding is transient, the detachment in Kr + Ne seeding is stable. It indicates that multi-species impurity seeding can be competitive for steady-state operation although further investigation is desired about the balance between divertor heat load reduction, impurity screening, and confinement degradation. The Kr emission enhancement is strongly affected by electron density and temperature at the last closed flux surface resulting in impurity penetration.